Skladový systém menší firmy - Hezoučký, Ladislav (Vysoké učení technické v Brně. Fakulta informačních technologií)
Práce je zaměřena na problematiku skladového systému menší firmy. Cílem je vytvořit funkční systém, který umožní zachytit podstatu operací na skladu ( příjmu a výdeje zboží, vystavení objednávek na zboží, vystavení faktur ). Systém je implementován pomocí HTML, PHP, JavaScriptu a MySQL.

This bachelor's thesis deals with store information system. The main goal of this thesis is to develop  a functional information system which will provide to catch the substance of operations in the stock ( stock receipt and stock out, draw purchase orders, draw invoice ). The system is implemented by using programming languages HTML, PHP and JavaScript. Database MySQL was choosen as a data storage.
Store Information System
Keywords: Skladový systém; informační systém; databáze; MySQL; PHP; Javascript; HTML; Store system; information system; database; MySQL; PHP; Javascript; HTML